Know when to fold ‘em: Polycomb complexes in oncogenic 3D genome regulation - Doyle, Emma J.; Morey, Lluis; Conway, Eric (Frontiers in Cell and Developmental Biology, 2022)
Chromatin is spatially and temporally regulated through a series of orchestrated processes resulting in the formation of 3D chromatin structures such as TADs, loops and Polycomb Bodies. These structures are closely linked to transcriptional regulation, with loss of control of these processes a frequent feature of cancer and developmental syndromes. One such oncogenic disruption of the 3D genome is through recurrent dysregulation of Polycomb Group Complex (PcG) functions either through genetic mutations, amplification or deletion of genes that encode for PcG proteins. PcG complexes are evolutionarily conserved epigenetic complexes. They are key for early development and are essential transcriptional repressors. PcG complexes include PRC1, PRC2 and PR-DUB which are responsible for the control of the histone modifications H2AK119ub1 and H3K27me3. The spatial distribution of the complexes within the nuclear environment, and their associated modifications have profound effects on the regulation of gene transcription and the 3D genome. Nevertheless, how PcG complexes regulate 3D chromatin organization is still poorly understood. Here we glean insights into the role of PcG complexes in 3D genome regulation and compaction, how these processes go awry during tumorigenesis and the therapeutic implications that result from our insights into these mechanisms.